Pengaruh Latihan High-Intensity Interval Training (HIIT) terhadap Peningkatan Daya Tahan Kardiovaskular (VO2Max) Atlet Bola Basket Mahasiswa Ilmu Keolahragaan - Rama Dani Saputra; Iman Imanuddin; Syam Hardwis (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine whether High-Intensity Interval Training (HIIT) has a significant effect on improving cardiovascular endurance (VO2Max) in basketball athletes among Sports Science students. The method used was a quantitative approach with a Pretest-Posttest Only Control Group Design, involving 20 samples selected from a population of 30 using the Simple Random Sampling technique, in which the experimental group was given HIIT treatment in the form of sprint interval training for 5 weeks (3 times per week, 80–90% intensity), while the control group received no treatment, and VO2Max was measured using the Multistage Fitness Test (Bleep Test), which was analyzed using the Shapiro-Wilk normality test, Levene's homogeneity test, and the independent t-test. The results showed significance values of (1) 0.002 in the pretest and (2) 0.000 in the posttest (both < 0.05), indicating a significant difference between the experimental and control groups. It can therefore be concluded that HIIT training has a significant effect on improving cardiovascular endurance (VO2Max) in basketball athletes among Sports Science students, with the experimental group showing a greater improvement than the control group. Keywords: Basketball, Basketball Athletes, Cardiovascular Endurance (VO2Max), High-Intensity Interval Training (HIIT)